Strategi pelayanan perusahaan PT. Kereta Api Indonesia (Persero) dalam meningkatkan pengguna jasa transformasi kereta api - Whis Alriz Luth'v; Bintang Adrian Sena Wangi; Rossa Amalia Lestari; Erina Effi Abidah; Eliya Salsabila; Andi Amri (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to determine the service strategy of the company PT. Kereta Api Indonesia (Persero) in increasing users of fire rubber transportation services. Based on the results of the study showed PT. Kereta Api Indonesia (Persero) has carried out a good SWOT analysis consisting of market strengths, weaknesses of this company, opportunities from the existence of railway products, and finally the threats that occur. In addition, researchers have studied further regarding the willingness to work in the current government, both permanent and contract employees. During the company's existence there has been an expansion of service offerings compared to the previous year, it has become commonplace by reducing the number of objections from customers who use these services. The most important thing is that there is a considerable effort on the part of the management to solve problems in serving the railways.